HUBUNGAN POLA ASUH ORANG TUA DENGAN HARGA DIRI ANAK USIA PRASEKOLAH - Siti Muniroh (STIKes William Booth Surabaya, 2017)
A preschool age (3 to 6 years ) is a golden period for children , whereby on this period children are very sensitive to absorb all information around them especially from their family or parents. The environment of the family is very important for the development of children’s self-esteem. Children who grow up in harmonious and religious family, parents who give love, attention and guidance in their life, hence the development of their self-esteem tends to be positive . The purpose of this research is to know the relationship between parent’s care patterns and pre school age children’s self esteem. This research used correlational with Cross Sectional approach. Thepopulation is all parents who have pre school age children on TKIT Ar Ruhul Jadid Sengon Jombang. This research used the samples taken from some parents who have pre school children on TKIT Ar Ruhul Jadid Sengon Jombang. This also used Purposive sampling technique. Data collection instrument in this research used questionnaires and structured interviews on bothvariables. Statistical tests used Spearman Rank with the level of significance (ρ ≤ 0,05). If the results obtained ≤ 0,05, the research hypothesis is accepted means there is relationship between the authoritative care patterns and the increasing of preschool children’s self esteem. It can be obtained from the research that most parents’ care patternsare authoritative is 26 respondents (74,29 %). There is almost entirely 34 respondents (97,14 % ) have positive self-esteem. From the data, can be obtained that α = 0,004 that α ≤ 0,05. SoHo rejected and H1 is accepted that means there is relationship between parent’s care patterns and pre school age children’s self esteem inTKIT Ar Ruhul Jadid. For all parents, is expected to be nurturing their children positively so the children will have the personality which is positive, more independent, mature and can they can appreciate theirselves properly.